Orchestrating Public Opinion : How Music Persuades in Television Political Ads for US Presidential Campaigns, 1952-2016. - Christiansen, Paul (Amsterdam University Press, 2017)
Analysis of political advertising tends to give music short shrift-which flies in the face of what we know about the power of music to set a mood, affect feelings, and influence our perceptions. This book is the first to offer a detailed exploration of the role of music in US presidential campaign advertising, from Eisenhower to the present, showing that in many cases music isn't simply one element in the presentation of an ad's message-it's the dominant factor, more important than images, words, or narration.